Pengaruh Payment Gateway dan Literasi Keuangan Terhadap Kinerja Keuangan Pada Pelaku UMKM di Kelurahan Kebonsari - Eriza Nabila Maharani; Anik Yuliati (CV. KAMPUS AKADEMIK PUBLISING, 2024)
MSMEs have an important contribution to Indonesia's economic growth by creating extensive employment opportunities and supporting a more equal distribution of income in society. This research aims to identify the impact of payment gateways and financial literacy on the level of financial performance of MSME players. This research applies an associative design and quantitative methods. Data collection was carried out by distributing questionnaires to MSMEs in Kebonsari Village. The results of this research show that both payment gateway (X1) and financial literacy (X2) have a positive and significant influence on the financial performance (Y) of MSMEs in Kebonsari Village.